STRATEGI KOMUNIKASI DALAM PEMBERDAYAAN MASYARAKAT TUNAGRAHITA OLEH “KARANGPATIHAN BANGKIT” DI RUMAH HARAPAN DESA KARANGPATIHAN PONOROGO - Aji, Landung Setia Wahyu; Aji, S.I.P., M.Si., Gilang Gusti (Universitas Negeri Surabaya, 2024)
Idiot Village in Karangpatihan Village is a unique place in Indonesia. The name Kampung Idiot emerged because many of the villagers were mentally retarded. Village and regional governments are trying to eliminate this term by providing empowerment through communication strategies to improve the quality of society. Karangpatihan Village provides a real example of how communities can develop and adapt in unexpected ways. This research aims to describe the empowerment communication strategy used by Karangpatihan Village. The method used is descriptive qualitative. Data was obtained from observations and interviews. The research results showed that the communication strategy used was face to face communication by approaching people with disabilities and inviting them to communicate using sign language created by the disabled themselves.